2021
DOI: 10.1007/s13167-021-00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Wrist actigraphic approach in primary, secondary and tertiary care based on the principles of predictive, preventive and personalised (3P) medicine

Abstract: Sleep quality and duration as well as activity-rest-cycles at individual level are crucial for maintaining physical and mental health. Although several methods do exist to monitor these parameters, optimal approaches are still under consideration and technological development. Wrist actigraphy is a non-invasive electro-physical method validated in the field of chronobiology to record movements and to allow for monitoring human activity-rest-cycles. Based on the continuous recording of motor activity and light … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…For the research of sleep and quality of sleep, the easy-to-use actigraphy is commonly used [ 89 , 90 ]. Actigraphy data from various studies have shown that there is a strong correlation between the changes in subjectively experienced CrF and sleep quality [ 2 , 10 , 16 ].…”
Section: State-of-the-artmentioning
confidence: 99%
“…For the research of sleep and quality of sleep, the easy-to-use actigraphy is commonly used [ 89 , 90 ]. Actigraphy data from various studies have shown that there is a strong correlation between the changes in subjectively experienced CrF and sleep quality [ 2 , 10 , 16 ].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Besides, circadian rhythms are useful for the treatment, prediction, and prevention of several physical and mental diseases including cardiovascular disease, myocardial ischemia, neurodegenerative disease, body microbiota, sleep–wake disorder, etc. [ 210 , 211 , 212 , 213 ].…”
Section: 3p Medicine and Variationsmentioning
confidence: 99%
“…Even worse, for each completed suicide, twenty other non-fatal suicide attempts can be considered statistically [8]. This unacceptable high number of cases further accentuates the utmost urgent need to promote and establish the principles of 3PM (for example see [9][10][11] also in psychiatric healthcare (see [12] for pharmacogenomics in the treatment of mood disorders)), especially predictive and preventive strategies in those associated with suicidality. In contrast to the risk for MDD, both suicidal risk and fatal suicide attempts are more strongly associated with the male sex [13].…”
Section: An Epidemiological Perspective On Depression and Suicidementioning
confidence: 99%